TINGKAT PARTISIPASI ANGGOTA KELOMPOK TANI TERHADAP PROGRAM PELAKSANAAN TANAM PADI GOGO RAWA DI DESA PEMULUTAN ULU KABUPATEN OGAN ILIR - Nur Azmee; R.A. Umikalsum; Anggraini Anggraini (Journal of Integrated Agribusiness, 2022)
This study aims to analyze the response, level of participation and factors that influence the level of participation of members of farmer groups who receive rice seed assistance in Pemulutan Ulu Village, Ogan Ilir Regency. The method used in this research is a survey method with a simple random sampling method from 306 farmers taken as much as 10% of the sample. Data analysis was performed by means of tabulation and multiple linear regression which was then explained descriptively. The results showed that the response of farmer group members to the implementation of the upland swamp rice planting program was in the medium category with a score of 53.33. The level of farmer participation is also in the moderate category with a score of 44.5. The utilization rate of upland rice assistance reaches 100%, but in terms of plant maintenance it is still low. Factors that significantly influence the level of participation are age, education, farming experience and number of dependents. While the factors that have no effect are land area, extension socialization and motivation.